MUSIC THERAPY IN RETT SYNDROME CASES - Andziule, Vita; Aleksiene, Vilmante; Lesinskiene, Sigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Rett syndrome is a rare (0,01%) genetic disorder affecting girls' development. Individuals with Rett syndrome experience a full range of health problems that severely influence and complicate their mobility, intellect, communication, learning, and entire lifestyle. The treatment of Rett's syndrome is still aimed at investigating new pathways to ensure the best possible patient’s development and quality of life. The distinctive feature of Rett syndrome is the two main sensations with little damage: hearing and vision. Therefore, music therapy plays an exceptional role in the treatment and special education of children with Rett syndrome. The goal of this study is to find the most effective music therapy techniques and their specific indications whilst working with individuals with Rett syndrome. Research method used: music therapists’ online survey conducted internationally. The research suggests that the most effective methods in Rett syndrome cases are structured musical games that promote targeted hands-on movements, as well as listening to the songs and choice of favourite songs using pictures or other symbols. Music therapy can be applied for various health needs of individuals with Rett syndrome, especially to enhance hand functions as well as to improve non-verbal communication and to help individuals experience togetherness and joy.